2002
DOI: 10.1016/s0020-7292(02)00147-9
|View full text |Cite
|
Sign up to set email alerts
|

Trends in twin births in New South Wales, Australia, 1990-1999

Abstract: A greater than expected increase in preterm twins was largely explained by an increase in elective deliveries at 35-36 weeks' gestation. Increasing maternal age does not appear to have contributed to the increase in preterm twin births. Lower rates of fetal death and low Apgar scores were achieved seemingly at the price of delivering more infants before term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 21 publications
1
16
0
Order By: Relevance
“…Our view is supported by trends in gestational age and the mode of delivery of twins from New South Wales, Australia [7] . During the period 1990 -1999, the percentage of twins born preterm ( < 37 weeks) increased from 40.8 to 48.8 % .…”
Section: Discussionsupporting
confidence: 52%
“…Our view is supported by trends in gestational age and the mode of delivery of twins from New South Wales, Australia [7] . During the period 1990 -1999, the percentage of twins born preterm ( < 37 weeks) increased from 40.8 to 48.8 % .…”
Section: Discussionsupporting
confidence: 52%
“…In all populations examined, maternal age at childbirth was increasing [22-25], caesarean delivery was becoming more common [23-26], and multiple pregnancy rates were also increasing [22,24,27]. The proportion of induced labors was noted to increase over a similar time period to the observed increase in PPH (Figure 3) [13,23,25,28].…”
Section: Resultsmentioning
confidence: 91%
“…Multiple pregnancy rates are also increasing [22,24,27]; possible contributory factors include assisted reproductive techniques and an aging population of women giving birth. Multiple pregnancy has been shown to be associated with an increased risk of PPH and associated complications in a number of studies [5,12,57,58] and thus the observed rise in the rate of multiple pregnancy may contribute to increasing PPH incidence.…”
Section: Discussionmentioning
confidence: 99%
“…Maternal outcomes analysed included diagnosis of gestational diabetes, gestation at diagnosis and type of treatment for gestational diabetes. Pregnancy outcomes included mode of birth, induction of labour, maternal hypertensive disorders (pre‐eclampsia, gestational hypertension and superimposed pre‐eclampsia) classified according to the Society of Obstetric Medicine of Australia and New Zealand , prematurity < 37 weeks' gestation, birthweight < 10th centile or birthweight > 90th centile (using twin birthweight centile charts ), congenital anomaly and perinatal death, a composite of stillbirth (birth with no signs of life ≥ 20 weeks' gestation or birthweight > 400 g) and neonatal death (any infant death within 28 days of birth). A composite adverse pregnancy outcome comprising preterm birth, birthweight < 10th centile, birthweight > 90th centile, birth trauma, perinatal death, pre‐eclampsia or gestational hypertension was also defined.…”
Section: Methodsmentioning
confidence: 99%